2017
DOI: 10.1007/s13253-017-0282-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale Modeling of Animal Movement and General Behavior Data Using Hidden Markov Models with Hierarchical Structures

Abstract: Hidden Markov models (HMMs) are commonly used to model animal movement data and infer aspects of animal behavior. An HMM assumes that each data point from a time series of observations stems from one of N possible states. The states are loosely connected to behavioral modes that manifest themselves at the temporal resolution at which observations are made. However, due to advances in tag technology, data can be collected at increasingly fine temporal resolutions. Yet, inferences at time scales cruder than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 34 publications
(34 reference statements)
2
89
0
Order By: Relevance
“…Coarse‐scale behavior identification, like the approaches demonstrated here, could be a first step in a hierarchical process of identifying fine‐scale behaviors (Leos‐Barajas et al, ). Several studies have been successful in distinguishing general behaviors, like the behaviors identified in this paper, but have been less successful in effectively classifying finer scale behaviors associated with prey capture, prey handling and self‐maintenance (Hammond et al, ; Ladds et al, ; Shamoun‐Baranes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Coarse‐scale behavior identification, like the approaches demonstrated here, could be a first step in a hierarchical process of identifying fine‐scale behaviors (Leos‐Barajas et al, ). Several studies have been successful in distinguishing general behaviors, like the behaviors identified in this paper, but have been less successful in effectively classifying finer scale behaviors associated with prey capture, prey handling and self‐maintenance (Hammond et al, ; Ladds et al, ; Shamoun‐Baranes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that the scale of these vertical excursions is large enough to allow classification at the daily time step. Therefore, we suggest that future studies either deploy more sophisticated tags which are capable of recording more refined information about the underlying movement process (e.g., accelerometers; Leos‐Barajas, Photopoulou, et al., ) or consider a nested hierarchical HMMs in which vertical and horizontal movements are recorded and classified at differing time scales (Leos‐Barajas, Gangloff, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hidden Markov models (HMMs) allow observed movements to serve as a proxy for the underlying behavioral states of interest, and further infer spatial and temporal effects of switching between behavioral states (Leos- Barajas et al, 2017;Patterson, Thomas, Wilcox, Ovaskainen, & Matthiopoulos, 2008). They assume a set of behaviors represented by movement are dependent on an unobserved state and can capture patterns found in movement data, which are translated as a proxy behavioral state.…”
Section: Hidden Markov Modelsmentioning
confidence: 99%